Business models in the search for efficiency: the case of public financial intermediaries. Issue 3 (16th April 2018) - Santandrea, Martina; Agasisti, Tommaso; Giorgino, Marco; Patrucco, Andrea S.
Abstract : This paper presents an optimal business model configuration for public financial intermediaries (PFIs). Using nonparametric techniques on Italian public financial corporations, the most efficient business models combined asset diversification and income specialization. These business models were unaffected by external financial turmoil, due to weak connections between PFIs and the traditional financial circuit; and public–private ownership is more efficient than purely public ownership, regardless of the business model adopted.